Lesbian ecologies: gardens, plants and queer animals in the artwork of Lila Jamieson, Trini Ibarra and Naomi Rincón-Gallardo - Escobedo Contreras, Larisa Itzel (2026)
Lila Jamieson is a lesbian painter stemming from the culture of hyper-masculinity and violence in the arid north of Mexico. In her paintings, she recreates a world filled with plants, kindness, and sweetness, depicting herself and her friends in colorful and affectionate settings. Trini Ibarra is a lesbian artist diagnosed with bipolar disorder who uses video art to create personal environments where nature, plants, animals, and water flow in her room to create heterotopic spaces that escape psychiatric and pharmacological violence that power seeks to exert over her body. Naomi Rincón Gallardo, presents queer narratives about fantastic animals to play and sing. Purpose: This work explores how women dissenting from compulsory heterosexuality seek to recreate alternative worlds for fulfilling lives, where art restores personal connections with the environment and serves as a shield against external hostility. Women who make their homes spaces of freedom, solidarity, and fulfillment. Women that are building a lesbian continuum and a gynocentric authonomy.